Clinicopathologic Presentation and Management of Malignant Orbito-ocular Tumors at a Tertiary Care Hospital in Nepal - Sthapit, Purnima Rajkarnikar; Amatya, Malita; Gurung, Hom Bahadur; Saiju, Rohit (Nepalese Journal of Ophthalmology, 2021)
Introduction: This study was conducted to evaluate the clinical presentations and management of various Orbito-ocular malignancies in Nepal. Materials and methods: This is a prospective study of ocular malignant cases conducted at a tertiary care eye hospital in Kathmandu, Nepal. One hundred and seventeen newly diagnosed eyes with ocular malignancy of 106 patients presenting to the clinic in a year from September 2018 to August 2019 were included for analysis. Patients’ demography, clinical features, various types of malignancies seen in eyes and their management were evaluated. Results: The mean age of patients was 30.35 years with a range from 1 month to 84 years and standard deviation of 26.63. 56% of the total were male. Red eyes and visible mass were the most common symptoms in 23% with intraocular contents in 48% being the most common site involved. Different types of ocular malignancies were detected, among which retinoblastoma was the most common in 38% of patients. Diagnosis in most patients was clinical and/or radiological; incision biopsy was required in 1.7% patients only. Surgical excision of the tumor was the most common treatment done in 29% followed by enucleation in 27% of eyes. Bilateral involvement of the eyes was seen in 10% of the patients. Conclusion: Malignant orbito-ocular tumors can be seen in any age group. Retinoblastoma is the commonest malignancy seen. With the help of imaging, diagnosis is near accurate; hence biopsy is not required in most cases before commencing treatment.